Letter: long‐term colorectal cancer incidence and mortality after adenoma removal associated with heritable factors, colonoscopic surveillance and aspirin—authors' reply. Issue 10 (26th April 2022) - Jodal, Henriette C.; Bretthauer, Michael; Kalager, Mette; Løberg, Magnus
LINKED CONTENT: This article is linked to Jodal et al papers. To view these articles, visit https://doi.org/10.1111/apt.16686 and https://doi.org/10.1111/apt.16922